THE EFFECT OF TAX ACCOUNTING CHOICES, DEBT POLICIES, AND OWNERSHIP CHARACTERISTICS OF TAX AGGRESSIVE IN MANUFACTURING COMPANIES ON THE IDX 2014-2018 - Anggun Putri Romadhina (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2020)
This study considers agreeing and obtaining evidence about the Difference between Tax Accounting Choices, debt policy and Characteristics of Ownership of Aggressive Taxes. This research was conducted at manufacturing companies published on the Indonesia Stock Exchange (IDX) in 2014-2018. This type of research is quantitative research that is associative in nature. This research was conducted on 136 manufacturing companies listed on the Indonesia Stock Exchange (IDX) using purposive sampling technique in determining research samples. Then obtained as many as 15 (fiveteen) manufacturing companies used as research samples. With observations for 5 (five) years, so the total observations in this study were 75 (seventy-five) audited financial statement data. The analysis technique used is descriptive statistical tests, classical assumptions test, and hypothesis testing. The results of this study indicate that the partial variable tax accounting choices do not affect the tax aggressiveness, this shows that the method of depreciation of the straight line or straight line does not affect the tax aggressiveness decision making. Debt policy against tax aggressiveness, this refers to the fact that questioning the company using funds from the company will reduce the amount of money that will incur a small interest fee that will occur in an aggressive tax action. Ownership characteristics do not affect the tax aggressiveness, this shows that the company owned by family or non-family does not affect the decision in tax aggressiveness. And simultaneously the tax accounting choice variable, debt policy and ownership characteristics affect the tax aggressiveness. Keywords: Tax Accounting Choices, Debt Policy, Characteristics of Ownership, Aggressive Taxes